2018
DOI: 10.22515/shirkah.v2i3.167
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Detection in the Banking System in Nigeria: Challenges and Prospects

Abstract: Fraud is an epidemic dimension that has eaten deep into the banking sector as well as the entire economics in Nigeria. Its devastating effect manifests itself in the deteriorating balance sheet of banks as well as in economic backwardness. Apparently, measures to detect and eradicate fraud in banking sector have been quite ineffective as the fraudulent practices have been on the increase in recent times. Thus, this study evaluates the various challenges of detecting and combating fraud in the banking sector in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Results found that moral development and education had a significant effect on fraud detection, while CPE on fraud has no effect on fraud detection. Finally, Badejo et al (2018), assessed the numerous difficulties in identifying and preventing fraud in Nigeria's banking industry. According to the findings of the descriptive research, the main type of fraud in Nigeria is the looting of funds by bank directors and managers rather than a lack of sufficient motivation.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Results found that moral development and education had a significant effect on fraud detection, while CPE on fraud has no effect on fraud detection. Finally, Badejo et al (2018), assessed the numerous difficulties in identifying and preventing fraud in Nigeria's banking industry. According to the findings of the descriptive research, the main type of fraud in Nigeria is the looting of funds by bank directors and managers rather than a lack of sufficient motivation.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Its severe effects may be seen in the declining bank income statement and the nation's economic downturn. Badejo, Okuneye, and Taiwo (2018), opined that, since deceptive activities have been increasing recently, it appears that efforts to identify and eliminate fraud in the financial sector have been largely ineffectual. Nugraha and Bayunitri (2020), describes fraud as "intentional activity by one or more individuals among management, staff, or third parties that might result in a financial statement deceit."…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations